Blunting of cardioprotective actions of estrogen in female rodent heart linked to altered expression of cardiac tissue chymase and ACE2. (July 2017) - da Silva, Jaqueline S.; Gabriel-Costa, Daniele; Wang, Hao; Ahmad, Sarfaraz; Sun, Xuming; Varagic, Jasmina; Sudo, Roberto T; Ferrario, Carlos M; Dell Italia, Louis J; Zapata-Sudo, Gisele; Groban, Leanne
Background: Diastolic dysfunction develops in response to hypertension and estrogen (E2) loss and is a forerunner to heart failure (HF) in women. The cardiac renin–angiotensin system (RAS) contributes to diastolic dysfunction, but its role with respect to E2 and blood pressure remain unclear. Methods: We compared the effects of ovariectomy (OVX) or sham surgery on the cardiac RAS, left ventricular (LV) structure/function, and systemic/intracardiac pressures of spontaneously hypertensive rats (SHRs: n = 6 intact and 6 OVX) and age-matched Wistar-Kyoto (WKY: n = 5 intact and 4 OVX) controls. Results: WKY rats were more sensitive to OVX than SHRs with respect to worsening of diastolic function, as reflected by increases in Doppler-derived filling pressures (E/e′) and reductions in myocardial relaxation (e′). This pathobiologic response in WKY rats was directly linked to increases in cardiac gene expression and enzymatic activity of chymase and modest reductions in ACE2 activity. No overt changes in cardiac RAS genes or activities were observed in SHRs, but diastolic function was inversely related to ACE2 activity. Conclusion: Endogenous estrogens exert a more significant regulatory role upon biochemical components of the cardiac RAS of WKY versus SHRs, modulating the lusitropic and structural components of its normotensive phenotype.